Complexes of aminobenzoic acids: A comprehensive review concerning synthesis, physical chemistry, structure and application - Kalembkiewicz, Jan; Kosińska, Małgorzata; Zapała, Lidia (Coordination chemistry reviews, 2017)
[Display omitted] •Aminobenzoic acids’ complexes with transition, post-transition and rare earth metals are reviewed.•A comprehensive survey of preparation, structure and physicochemical properties of the complexes is included.•Some important potential applications of the complexes are outlined. The literature studies on the complexes of aminobenzoic acids, especially fenamates, with transition, post-transition and rare earth metals reveal a great interest in this subject. In this paper the binary and ternary complexes of aminobenzoic acids involving oxygen-, nitrogen- and phosphorus-donor coligands were described. We compared the complexes’ synthesis methods, their physicochemical properties, spectroscopic studies as well as composition and geometry. The complexes have been characterized in terms of their biological activity and applications as medicals, hybrid organic–inorganic materials, luminescent materials, green corrosion inhibitors, catalysts and magnetic materials.